Highly Temperature‐Stable Carbon Nanotube Transistors and Gigahertz Integrated Circuits for Cryogenic Electronics. (3rd June 2021) - Xie, Yunong; Zhong, Donglai; Fan, Chenwei; Deng, Xiaosong; Peng, Lian‐Mao; Zhang, Zhiyong
Abstract: Cryogenic electronics are attracting more and more attentions owing to the rising of space exploration and quantum computing, in which low‐temperature stable operation is even more concerned than performance of the integrated circuits (ICs). As a promising semiconducting material, carbon nanotube (CNT) has been extensively explored on its low‐temperature transport characteristics, but the cryogenic electronics application of CNT transistors and ICs has seldom been demonstrated. In this work, the low‐temperature operation of field‐effect transistors (FETs) and ICs built on solution‐derived high semiconducting purity randomly oriented CNT film is investigated. The randomly oriented CNT FETs exhibit much higher temperature stability than the individual CNT based FETs and Si transistors from room temperature to liquid nitrogen temperature, and then the ICs constructed by the CNT film FETs present excellent temperature‐stability. Specifically, the fabricated five‐stage ring oscillators (ROs) exhibit oscillation frequency up to 1.5 GHz with the performance change less than 0.5% at the temperature ranging from 300 to 80 K. The work reveals the great potential of high‐performance transistors and ICs built on randomly oriented CNT films in cryogenic electronics applications. Abstract : The great potential of randomly oriented CNT film‐based ICs in cryogenic electronics applications is explored. The solution‐derived network CNT FETs exhibit much higher temperature stability than the individual CNT based FETs and Si transistors from room temperature to liquid nitrogen temperature. ROs constructed by these FETs exhibit the maximum oscillation frequency up to 1.5 GHz and present excellent temperature stability, i.e., oscillation frequency change is within 0.5% at the temperature ranging from 300 to 80 K.